SCREENING AND IDENTIFICATION ALKALY-CELLULOLYTIC MOLDS FROM RICE STRAW ON COASTAL-FIELD OF WATU ULO JEMBER - Esti Utarti; Su’udah Hasanah; Siswanto Siswanto (Jurnal ILMU DASAR, 2012)
About 28 molds were obtained from rice straw on coastal-field of Watu Ulo Jember, were screened for their cellulolytic activities at pH alkaline. In semiquantitatively screening on CMC and Avicel plate at pH 8 showed that 27 isolates have cellulolytic activities. Based on clearing zone in CMC plate, isolates 7, 9, 14, 19 and 24 have higher cellulase (CMC-ase) activities index at pH alkaline. Further, in quantitatively examination using rice straw in Basic Salt Mandel’s modification medium showed isolate 19 (0,60 U/ml) that identified as Aspergillus terreus have higher FP-ase activity than isolate 7  (0,56 U/ml), 9  (0,55 U/ml), 14 (0,53 U/ml) and 24 (0,56 U/ml).